Transformational Leadership in Teaching: Mier y Pesado School, a Case Study - Meza-Mejía, Mónica del Carmen (2014)
The present research is founded on the premise that in a school, the teacher is a leader and must be perceived as such to manage the classroom in order to make things happen. The case under study uses an exploratory-descriptive methodology to analyze whether the teachers Mier y Pesado School, located in Mexico City, perceive having any of the characteristics from Transformational Leadership (TL). Regarding this question, the researchers’ perception leads to two hypotheses: 1) the higher the teachers’ educational level is, the more TL characteristics they have; 2) the more teaching experience teachers have, the more LT characteristics they have acquired throughout the years. The data collection instrument used was a questionnaire. Among the limitations of the study, it can be noted that the correlations –between teaching experience, educational level and LT characteristics-- were not significant for the proposed hypotheses due to the small sample size used. However, future research is encouraged by applying the questionnaire with a larger sample.